Targeting Protein-Protein Interactions by Small Molecules - Sheng, Chunquan; Georg, Gunda I.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book comprehensively reviews the state-of-the-art strategies developed for protein-protein interaction (PPI) inhibitors, and highlights the success stories in new drug discovery and development. Consisting of two parts with twelve chapters, it demonstrates the design strategies and case studies of small molecule PPI inhibitors. The first part discusses various discovery strategies for small molecule PPI inhibitors, such as high throughput screening, hot spot-based design, computational approaches, and fragment-based design. The second part presents recent advances in small molecule inhibitors, focusing on clinical candidates and new PPI targets. This book has broad appeal and is of significant interest to the pharmaceutical science and medicinal chemistry communities. .
Part 1 Current strategies for the discovery of small-molecule inhibitors of protein-protein interactions -- Overview of Protein-protein Interactions and Small Molecule Inhibitors under Clinical Development -- High throughput screening in the discovery of small molecule inhibitors of protein-protein interactions -- Hot Spot-Based Design of Small-Molecule Inhibitors for Protein-Protein Interactions -- Computational Methods Applicable to the Discovery of Small-Molecule Inhibitors of Protein-Protein Interactions -- Experimental Methods Used for Identifying Small-Molecule Inhibitors of Protein-protein Interaction -- Fragment-based Drug Discovery for Developing Inhibitors of Protein-protein Interactions -- Part 2 Case studies of small-molecule inhibitors of protein-protein interactions -- Small molecule inhibitors targeting new targets of protein-protein interactions -- The Development of New Spirooxindoles Targeting the p53-MDM2 Protein-Protein Interactions for Cancer Therapy -- Small-Molecule Inhibitors for the β-Catenin/T-Cell Factor Protein−Protein Interaction -- Discovery and development of Keap1-Nrf2 protein-protein interaction inhibitors -- BRDT Inhibitors for Male Contraceptive Drug Discovery: Current Status -- Targeting Protein-Protein Interactions in Small GTPases.
Keywords: Medicinal chemistry; Pharmaceutical chemistry; Bioorganic chemistry; Proteins .; Medicinal Chemistry; Pharmaceutics; Bioorganic Chemistry; Protein Biochemistry